Influence of Plant Bio-regulators on Physiological Traits, Gas Exchange and Yield of Clusterbean (Cyamopsis tetragonoloba L. Taub) under Water Stress - Nathawat, N.S.; Bhardwaj, S.; Singh, J.P.; Rathore, V.S.; Yadava, N.D. (Annals of Arid Zone, 2023)
Clusterbean (Cyamopsis tetragonoloba L.Taub) is the most important summerlegume crop grown in hot arid regions. However, little is known of its morphological,physio-biochemical responses, and yield traits to drought and sulphydryl compounds(-SH compounds) application. Drought had significant negative effects on growth andmetabolism, as revealed by reduced leaf area, net assimilation rate, leaf relative watercontent photosynthetic rate, photosynthetic pigments and weakened yield traits. A fieldexperiment was conducted for two consecutive years to investigate the effect of foliarapplication of two plant bio-regulators (PBR’s) applied at different concentrations namely,thioglycollic (TGA) acid at 200 mg L-1, 300 mg L-1 and 400 mg L-1; thiourea at 500 mgL-1, 750 mg L-1 and 1000 mg L-1 on morpho-physiological traits and yield parameters.Foliar application of PBRs at different concentrations increased 16-35%, 11-20%, 9-30%,8-39% and 14-21% higher growth attributes, water relations, photosynthetic pigments,gas exchange parameters, and seed yield, respectively. Although eliciting behaviorof bio-regulators improved morpho-physiological attributes against drought stresscondition, the application of TGA 400 mg L-1 and TU 1000 mg L-1 recorded maximumnet assimilation rate, leaf area, RWC, total chlorophyll, carotenoid content, pods, 100seed weight and seed yield over control.